2010
DOI: 10.1186/1477-7819-8-82
|View full text |Cite
|
Sign up to set email alerts
|

Young patients with colorectal cancer have poor survival in the first twenty months after operation and predictable survival in the medium and long-term: Analysis of survival and prognostic markers

Abstract: ObjectivesThis study compares clinico-pathological features in young (<40 years) and older patients (>50 years) with colorectal cancer, survival in the young and the influence of pre-operative clinical and histological factors on survival.Materials and methodsA twelve year prospective database of colorectal cancer was analysed. Fifty-three young patients were compared with forty seven consecutive older patients over fifty years old. An analysis of survival was undertaken in young patients using Kaplan Meier gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
3
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 16 publications
5
47
3
2
Order By: Relevance
“…Colorectal cancer (CRC) is the commonest malignancy in the gastrointestinal tract (Chan et al, 2010) and common diagnosed cancer in both men and women. It is the third leading cause of cancer dependent death in the world and there are one million new cases diagnosed per year (Ranjbar1 et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the commonest malignancy in the gastrointestinal tract (Chan et al, 2010) and common diagnosed cancer in both men and women. It is the third leading cause of cancer dependent death in the world and there are one million new cases diagnosed per year (Ranjbar1 et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A twelve year prospective database of colorectal cancer patients was analyzed by Chan et al to compare the clinico-pathological features in young (<40 years) and older (>50 years) patients. They observed that duration of symptoms and clinical presentation was similar in both groups [22]. Another comparative study on the clinico-pathological features of colorectal malignancies in Sri Lankan patients aged 40 years or younger and older patients conducted by De Silva et al reported that there is no difference in clinical presentation between the 2 groups.…”
Section: Characterization Of Cancer Syndromes In Sri Lankamentioning
confidence: 91%
“…In another study, the same value has been found to be. 10 3 months. 17 In our study, however, the mean survival rate for gastric cancer patients for 13.9± 7.8 months of follow-up was found to be 11.7±6.7 months.Our findings are in harmony with the literature.…”
Section: 8mentioning
confidence: 99%
“…Among the reasons for that, late diagnosis, advanced phase of tumors at the moment of diagnosis, and their more invasive, more aggressive and undifferentiated structure may be specified. 5,[7][8][9][10] Since the young adults seem healthier and cancer is generally recognized as the disease of advanced ages, the diagnosis is delayed and the disease is diagnosed in further phases 9 .…”
Section: Introductionmentioning
confidence: 99%